Individual Gas Molecules Detection Using Zinc Oxide–Graphene Hybrid Nanosensor: A DFT Study - Ingrid Torres; Sadegh Mehdi Aghaei; Amin Rabiei Baboukani; Chunlei Wang; Shekhar Bhansali (C, 2018)
Surface modification is a reliable method to enhance the sensing properties of pristine graphene by increasing active sites on its surface. Herein, we investigate the interactions of the gas molecules such as NH3, NO, NO2, H2O, and H2S with a zinc oxide (ZnO)–graphene hybrid nanostructure. Using first-principles density functional theory (DFT), the effects of gas adsorption on the electronic and transport properties of the sensor are examined. The computations show that the sensitivity of the pristine graphene to the above gas molecules is considerably improved after hybridization with zinc oxide. The sensor shows low sensitivity to the NH3 and H2O because of the hydrogen-bonding interactions between the gas molecules and the sensor. Owing to observable alterations in the conductance, large charge transfer, and high adsorption energy; the sensor possesses extraordinary potential for NO and NO2 detection. Interestingly, the H2S gas is totally dissociated through the adsorption process, and a large number of electrons are transferred from the molecule to the sensor, resulting in a substantial change in the conductance of the sensor. As a result, the ZnO–graphene nanosensor might be an auspicious catalyst for H2S dissociation. Our findings open new doors for environment and energy research applications at the nanoscale.